2011
DOI: 10.3390/w3041005
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Ocean Acidification on Reproduction, Early Development and Settlement of Marine Organisms

Abstract: Predicting the impact of warming and acidifying on oceans on the early development life history stages of invertebrates although difficult, is essential in order to anticipate the severity and consequences of future climate change. This review summarises the current literature and meta-analyses on the early life-history stages of invertebrates including fertilisation, larval development and the implications for dispersal and settlement of populations. Although fertilisation appears robust to near future predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
126
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(130 citation statements)
references
References 126 publications
3
126
1
Order By: Relevance
“…In general, non-calcifying autotrophs might benefit from higher CO 2 availability, while calcifying organisms, apart from crustaceans, are negatively impacted, with bivalves and echinoderms being among the most vulnerable groups [7,8,10,11]. However, ocean pCO 2 itself varies considerably with space, depth and time [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, non-calcifying autotrophs might benefit from higher CO 2 availability, while calcifying organisms, apart from crustaceans, are negatively impacted, with bivalves and echinoderms being among the most vulnerable groups [7,8,10,11]. However, ocean pCO 2 itself varies considerably with space, depth and time [17].…”
Section: Introductionmentioning
confidence: 99%
“…Although it is still uncertain how these changes will impact the biological systems, their effects will likely vary among both taxa and life stages [7]. Larval stages, especially in calcifying species, are thought to represent the life-cycle bottleneck most vulnerable to OA [7][8][9][10][11]. They may be more sensitive to perturbations due to low energy storage levels, potential disruptions in development of vital structures, and possible delays in metamorphosis, which may increase vulnerability to predators or affect transport mechanisms, removing them from suitable habitats [12].…”
Section: Introductionmentioning
confidence: 99%
“…The finding that simulated ocean acidification had no significant effects on the growth and skeletal structure of the adult stages of two widespread cold-water corals [3], but can be particularly severe for organisms which start to calcify in their larval and/or juvenile stages [1] and there may also be indirect effects through loss of food quality since rising CO2 levels affect the biochemistry of phytoplankton [7,8] highlights the fact that there is likely to be significant variations in species' responses. The otoliths of squid embryos are affected by the combined effects of acidification and lowered oxygen, although conditions within the brood capsule also affect their geochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…Pauline Ross and colleagues at the University of Western Sydney and the Port Stephens Fisheries Centre in Australia produced a review of the effects of ocean acidification on the early life-history stages of invertebrates including fertilisation, larval development and the implications for dispersal and settlement of populations [1]. They concluded that although fertilisation appears robust to near future predictions of ocean acidification, larval development is much more vulnerable across major invertebrate groups such as molluscs and echinoderms.…”
Section: The Modulating Role Of Evolution and The Need For Long Term mentioning
confidence: 99%
See 1 more Smart Citation